Working capital management efficiency: A study of certified firms from the EFQM Excellence Model - Yousaf, Muhammad (Financial Internet Quarterly, 2022)
Working capital management (WCM) plays an important role in a firm's value, financial risk, and firm profitability. WCM requires continuous management to maintain a certain level of the numerous components of working capital (WC). The main aim of this study is to estimate the efficiency of WCM of certified firms from the European Foundation for Quality Management (EFQM) Excellence Model. The study also tests the speed to attain each firm's target level of efficiency using industry norms as the target level of efficiency. The financial data of the Czech certified firms from the manufacturing sector was derived from the CRIBIS database from 2015 to 2020. The efficiency of WCM is measured by utilization index (UI), performance index (PI), and efficiency index (EI). The findings revealed that Gerresheimer Horsovsky Tyn Spol., Miele Technika, and Koyo Bearings éCeská Republika efficiently managed WC, as their indexes are greater than 1. The number of efficient firms was the lowest in 2020 based on the year-wise comparison which means that the efficiency of WCM of the firms was severely affected by the coronavirus pandemic (COVID-19). All the Ø values are lower than one, which signifies that none of the selected firms outperform the manufacturing industry as a whole.